2008
DOI: 10.1037/a0013192
|View full text |Cite
|
Sign up to set email alerts
|

A new look at the consequences of attitude certainty: The amplification hypothesis.

Abstract: It is well established that increasing attitude certainty makes attitudes more resistant to attack and more predictive of behavior. This finding has been interpreted as indicating that attitude certainty crystallizes attitudes, making them more durable and impactful. The current research challenges this crystallization hypothesis and proposes an amplification hypothesis, which suggests that instead of invariably strengthening an attitude, attitude certainty amplifies the dominant effect of the attitude on thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 56 publications
11
100
0
Order By: Relevance
“…As suggested earlier, (un)certainty has already been distin guished from ambivalence by various researchers (e.g., Bassili, 1996;Clarkson et al, 2008;Rucker & Petty, 2004;Rucker et al, 2008). Shepherd, Kay, Landau, and Keefer (2011) recently showed that different psychological threats elicit different kinds of com pensatory coping responses.…”
Section: Discussionmentioning
confidence: 93%
“…As suggested earlier, (un)certainty has already been distin guished from ambivalence by various researchers (e.g., Bassili, 1996;Clarkson et al, 2008;Rucker & Petty, 2004;Rucker et al, 2008). Shepherd, Kay, Landau, and Keefer (2011) recently showed that different psychological threats elicit different kinds of com pensatory coping responses.…”
Section: Discussionmentioning
confidence: 93%
“…Ambivalence is a central construct in the literature on attitudes, and it has been the focus of a recent resurgence in research interest (e.g., Cavazza & Butera, 2008;Clark et al, 2008;Clarkson, Tormala, & Rucker, 2008;Cowley & Czellar, 2012;DeMarree, Morrison, Wheeler, & Petty, 2011;Hormes & Rozin, 2011;Petty, Tormala, Briñol, & Jarvis, 2006;Priester et al, 2007;Sawicki et al, 2013;Schneider et al, 2013;van Harreveld, Rutjens, et al, 2009;Ziegler, Schlett, Casel, & Diehl, 2012). Although the subjective experience of conflict is important because it often drives ambivalence outcomes (e.g., attitudebehavior correspondence, information seeking), there is a current gap in our understanding of the factors that contribute to this sense of conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Under the guise of an "autobiographical memory" task, participants were randomly assigned to describe three experiences that made them feel either very certain or very uncertain. They received these instructions (adapted from Clarkson, Tormala, & Rucker, 2008 Next, as part of a "text comprehension" task, participants completed the same conceptual perspective-taking task involving ambiguous e-mail messages that we used in Experiment 3 (Keysar, 1994).…”
Section: Experiments 4b: Uncertainty ¡ Egocentrismmentioning
confidence: 99%